2019
DOI: 10.1038/s41598-019-56999-3
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Carboxymaltose in the treatment of chemotherapy-induced anaemia: an effective, safe and cost- sparing alternative to blood transfusion

Abstract: Anaemia is highly prevalent in cancer patients, adversely affects quality of life and impacts survival. The pathogenesis is multifactorial, with iron deficiency being a major and potentially treatable contributor. This study aimed to assess the effectiveness and economic impact of ferric carboxymaltose in chemotherapy-induced anaemia. This prospective cohort study between 2015–2016 of chemotherapy-treated patients for solid tumours, grade ≥2 anaemia and iron deficiency evaluated hematopoietic response four wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A multi-center observational study has shown that ferric carboxymaltose treatment significantly decreased transfusion rates among patients with colon cancer (9.9 vs. 38.7%; p < 0.001) [30]. Another prospective study conducted in Portugal between 2015 and 2016 showed a 26% decrease in the transfusion rate compared to the historical control group [31].…”
Section: Discussionmentioning
confidence: 99%
“…A multi-center observational study has shown that ferric carboxymaltose treatment significantly decreased transfusion rates among patients with colon cancer (9.9 vs. 38.7%; p < 0.001) [30]. Another prospective study conducted in Portugal between 2015 and 2016 showed a 26% decrease in the transfusion rate compared to the historical control group [31].…”
Section: Discussionmentioning
confidence: 99%
“…4,[15][16][17][18][19] For IVFC, we assumed a dose of 750mg delivered twice over the course of one week. 6,7,[20][21][22][23] We constructed a separate model to assess the costs associated with the most common adverse reactions to each iron therapy (Supplemental).…”
Section: Costsmentioning
confidence: 99%
“…The incidence of anemia in patients with cancer varies from 20%-60% at the time of diagnosis to 60%-90% during cancer treatments. 34 The pathogenesis of IDA in cancer is multifactorial, ranging from inadequate dietary intake, inflammation, myelosuppression with chemotherapy and bone marrow infiltration by tumor cells to blood loss during surgery. 8 Anemia in these patients results in symptoms that affect quality of life, such as mental confusion, depression, nausea, and loss of appetite.…”
Section: Iron Deficiency Anemia In Women With Cancermentioning
confidence: 99%